Influence of some abiotic factors on the activity patterns of trapdoor spiders, scorpions and camel spiders in a central South African grassland. Issue 2 (4th May 2019) - Neethling, Jan A.; Haddad, Charles R.
Abstract : Trapdoor spiders (Araneae: Mygalomorphae), scorpions (Scorpiones) and camel spiders (Solifugae) were collected by pitfall trapping from an undisturbed grassland area within the Free State National Botanical Gardens, with the aim of analysing the effects of rainfall, temperature and lunar incidence on their activity patterns. During the study a total of 8109 non-acarine arachnids were collected, of which Mygalomorphae, Solifugae and Scorpiones represented only 5.04% ( n  = 409). Mygalomorph spiders ( n  = 195) were represented by four families and five species, namely Ancylotrypa dreyeri (Hewitt, 1915) (Cyrtaucheniidae), Stasimopus oculatus Pocock, 1897 and S. minor Hewitt, 1915 (Ctenizidae), Segregara sylvestris (Hewitt, 1925) (Idiopidae) and Calommata meridionalis Fourie, Haddad and Jocqué, 2011 (Atypidae). Scorpions ( n  = 71) were represented by two buthid species, Uroplectes triangulifer (Thorell, 1876) and U. carinatus (Pocock, 1890). Solifugae ( n  = 153) were represented by Solpugema coquinae orangica (Hewitt, 1919) and Solpugassa sp. (Solpugidae). Rainfall and temperature were the main factors influencing seasonal variations in activity, with lunar incidence having no detectable effect. Uroplectes triangulifer and Solpugema coquinae orangica were the only species active during late winter and early spring, prior to the first significant rains in mid-spring. After emerging, populations of most species rapidly increased to a peak before declining again.